Benefit Evaluation of Comprehensive Reform in Agricultural Water Prices Based on AHP-CRITIC-Fuzzy Comprehensive Evaluation - LI Shu; LONG Yan; FENG Mengjuan; ZHANG Haosen; LI Youming; MA Fangping; CHEN Jianghai (Renmin Zhujiang)
In recent years,the reform of agricultural water prices has attracted wide attention from all walks of life,and it is also a difficulty in water conservancy reform and comprehensive rural reform.In this paper,Dengkou County of Inner Mongolia is taken as the research area,and a benefit evaluation system for comprehensive reform of agricultural water prices is constructed.The system covers four criterion layers,i.e.,water conservation,economy,society,and ecology,and 14 indexes.Then,the comprehensive weight of each index is determined by the combination of analytic hierarchy process (AHP) and CRITIC,and the fuzzy comprehensive evaluation method is used to evaluate the benefits of agricultural water price reform in Dengkou County from 2017 to 2020.The evaluation results suggest that during the four years,the benefits of agricultural water price reform in Dengkou County show a positive trend in general;among them,social benefits are the best,followed by water conservation benefits,and the economic and ecological benefits do not undergo a signficant increase.Moreover,it is pointed out that improving irrigation water efficiency and reducing agricultural water expenditure are the main influencing factors of water price reform.